Using e‐learning modules to teach ongoing‐visual inspection of functional analyses. Issue 4 (8th May 2020) - Retzlaff, Billie J.; Phillips, Lauren A.; Fisher, Wayne W.; Hardee, Alexandra M.; Fuhrman, Ashley M.
Abstract : Despite the effectiveness of function‐based treatments, most clinicians do not conduct functional analyses (FA). The time required to conduct an FA is a major barrier preventing their use. One way to increase FA efficiency is to discontinue the analysis as soon as it has produced clear results. Saini et al. (2018) evaluated a structured procedure for ongoing‐visual inspection of FAs and found that it produced accurate interpretations while averaging 40% fewer sessions than author interpretation. This study evaluated the efficacy of an e‐learning module for training registered behavior technicians (RBTs) to implement ongoing visual inspection of FAs. Following training, 5 of the 6 participants showed mastery of ongoing visual inspection, and the final participant did so with the addition of supplemental procedures. We discuss how this training may increase the efficiency of FAs by teaching individuals who are less experienced in FA methodology when to seek supervision from a supervising Board Certified Behavior Analyst® (BCBA).